Natural outcome of cannabis use disorder: a 3‐year longitudinal follow‐up. (26th August 2015) - Feingold, Daniel; Fox, Jonah; Rehm, Jürgen; Lev‐Ran, Shaul
Abstract: Aims: To assess the prevalence and correlates of remission from cannabis use disorders (CUDs), focusing on the proportion of individuals with CUDs that remit without abstaining from cannabis use. Design: Three‐year longitudinal study. Setting: Wave 1 (2001) and wave 2 (2004) of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a nationally representative sample of US adults aged 18 years and over. Participants: Our sample included 444 individuals diagnosed with DSM‐IV cannabis abuse and/or dependence during the 12 months prior to wave 1 of the NESARC. Measurements: Baseline socio‐demographic and clinical correlates were analysed for possible outcomes of CUDs after 3 years: abstinent remission, non‐abstinent remission and sustained disorder. Findings: Approximately two‐thirds (67%) of individuals with baseline CUD remitted at follow‐up. Approximately 37% of those who remitted were non‐abstinent. Remission was associated with Hispanic ethnicity [odds ratio (OR) = 2.59; 95% confidence interval (CI) = 1.27–4.87], baseline daily or almost daily use of cannabis (OR = 1.91; 95% CI = 1.15–3.16), baseline use of other drugs (OR = 1.63; 95% CI = 1.04–2.56) and two or more medical conditions at baseline (OR = 8.40; 95% CI = 2.67–26.41). Non‐abstinent remission was associated with baseline daily or almost daily use of cannabis (OR = 1.92; 95% CI = 1.05–3.51). Conclusions: A substantial level of remission from cannabis use disorders (CUDs), including non‐abstinent remission, suggests that the nature of CUDs may be more unstable than reported previously.